Evolution of a taboo: pigs and people in the Ancient Near East - Price, Max D. ca. 20./21. Jh. (Oxford University Press, 2020)
"From their domestication to their taboo, the role of pigs in the ancient Near East is one of the most complicated topics in archaeology. Rejecting monocausal explanations, this book adopts an evolutionary approach and uses zooarchaeology and texts to unravel the cultural significance of swine from the Paleolithic to today. Five major themes emerge: The domestication of the pig from wild boar in the Pre-Pottery Neolithic, the unique roles that pigs developed in agricultural economies before and after the development of complex societies, the raising of swine in cities, the shifting ritual roles of pigs, and the formation and development of the pork taboo in Judaism and, later, Islam. The development of this taboo has inspired much academic debate. I argue that the well-known taboo described in Leviticus reflects the intention of the Biblical writers to develop an image of a glorious pastoral ancestry for a heroic Israelite past, something they achieved by tying together existing food traditions. These included a taboo on pigs, which was developed early in the Iron Age during conflicts between Israelites and Philistines and was revitalized by the Biblical writers. The taboo persisted and mutated, gaining strength over the next two and a half millennia. In particular, the pig taboo became a point of contention in the ethno-political struggles between Jewish and Greco-Roman cultures in the Levant. Ultimately, it was this continued evolution within the context of ethnic and religious politics that gave the pig taboo the strength it has today"--